2022
DOI: 10.3389/fvets.2022.852407
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes and Their Structural Relationships With the Sperm Storage Tube and Surrounding Cell Types in the Utero-Vaginal Junction of the Chicken

Abstract: Telocytes (TCs) are a new type of mesenchymal cells that have been discovered recently in many organs and tissues. However, studies of TCs in the avian reproductive system are still at the beginning. Chickens are one of the world's most popular domesticated animals, providing inexpensive but valuable proteins and nutrients from chickens and eggs to nourish the human bodies. Chickens have important scientific value; thus, understanding the reproductive system regulations seems to be important. The utero-vaginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Taking into account their proangiogenic capacity, the authors hypothesized that telocytes could contribute to tumor formation. Telocytes were recently studied in the uterovaginal junction of the chicken [8]. Transitioning back to human studies, Abu-Dief et al [9] researched placental telocytes in preeclampsia and revealed that in patients with preeclampsia, the telocyte population in the chorionic villi, decidua, and myometrium was significantly decreased, potentially contributing to the pathogenesis of this serious condition.…”
mentioning
confidence: 99%
“…Taking into account their proangiogenic capacity, the authors hypothesized that telocytes could contribute to tumor formation. Telocytes were recently studied in the uterovaginal junction of the chicken [8]. Transitioning back to human studies, Abu-Dief et al [9] researched placental telocytes in preeclampsia and revealed that in patients with preeclampsia, the telocyte population in the chorionic villi, decidua, and myometrium was significantly decreased, potentially contributing to the pathogenesis of this serious condition.…”
mentioning
confidence: 99%